Pre-stack time migration in common source domain without velocity model - Khoshnavaz, M.; Bona, Andrej; Urosevic, Milovan (2015)
Most of the migration techniques require an input velocity model. Velocity analysis is one of the most critical stages in seismic data processing. Standard ways to find the velocity model are constant velocity stack and semblance velocity analysis, which can be time consuming and labour intensive. In this paper, we introduce another approach to obtain the migration velocity and pre-stack time migration algorithm that is time effective and does not require any input velocity model prior to imaging. The velocity in each point in a common source gather is derived by calculating the radius of the curvature of seismic reflected wave-front. The velocity is independent of of two way travel time and offset. It makes it also suitable for passive seismic imaging and earthquake seismology. The feasibility of the proposed technique is demonstrated on both synthetic and field seismic data examples.